PENINGKATAN KINERJA DAN MITIGASI RISIKO RANTAI PASOK AGROINDUSTRI NANAS DI PT GREAT GIANT PINEAPPLE - Marimin Marimin; Muhammad Iqbal Muzakki (Jurnal Teknologi Industri Pertanian, 2021)
Indonesia as one of the biggest pineapple exporters has many competitors in international market. One of the exporters of pineapple product is Great Giant Pineapple Company which has integrated farm and industries. Furthermore, there is a chance for risk to occur in pineapple agroindustry supply chain. According to the case mentioned, a company should make effort to maintaining its supply chain stability. This research aimed to improve the performance and mitigates risks through performance and risk analysis at Great Giant Pineapple Co. The methods used in this research were SCOR-fuzzy-AHP for performance measurement, HOR for risk analysis, and ANP-SWOT for strategy selection. The result for performance measurement in Great Giant Pineapple Co. for its plantation and canned pineapple industry in 2018 were 95.66% and 91.28%, respectively, while in 2019 were91.45% and 94.57%, respectively. Risk analysis identified 22 risk events and 15 risk agents. Nine of the risk agents were prioritized based on ARP score. There were 11 action that were proposed to reduce the risk. Mitigation action that should be done first was enhancing the competencies of workers through training caused of cost effectiveness. Performance improvement was defined by considering the analysis of internal and external factor that the company had. Based on expert’s assessments, empowering technology to improve production speed and flexibility is the most influential strategy.Keywords: performance, pineapple agroindustry, risk, supply chain